Complex anal fistulae management by combined technique approach: an experience - M. E., Shaileshkumar; P. T., Sushanth (International Surgery Journal, 2018)
Background: The aim of this study is to evaluate our experience in the management of complex anal fistulae by combined technique approach. Ideal surgical treatment for complex anal fistula should aim to eradicate the source of infection and promote healing of the tract, while preserving the sphincters and the mechanism of anal continence. Even with the evolving newer techniques complex anal fistulae have higher rates of recurrence and functional disability as anal incontinence. The requirement of multiple surgeries for recurrence and the newer techniques like anal fistula plug are expensive and will become a burden for patients living in developing countries like ours. Thus, apart from Ligation of Intersphincteric fistula tract, the use of cutting seton is the main surgical method practiced here. This article focuses on the approach to the complex anal fistula management through evidence-based treatment strategies. Methods: Author conducted a prospective study of 35 complex anal fistulae patients undergoing combined technique approach with cutting Seton, Ligation of Intersphincteric Fistula tract and fistulotomy. Results: All patients recovered well with no complications in postoperative period. After 2 years of follow up patients are recurrence free and only 2 patients had partial incontinence with improving trend. Conclusions: The use of cutting Seton in high anal fistula is an effective technique. LIFT technique is good for Transphincteric tracts without previous scarring; it can be easily learned and applied. We can conclude that combined technique was an effective procedure and valid alternative for complex anal fistula management.